Global Provisioning of Red Meat for Flexitarian Diets - Hicks, Talia M.; Knowles, Scott O.; Farouk, Mustafa M. (Frontiers in Nutrition, 2018)
Although not always labeled as such, flexitarianism is the default lifestyle for much of the world, whereby meals based on plant materials provide the bulk of people’s calories. The rich nutrition of meat and animal products is often the lynchpin of these diets, even when only consumed occasionally. It provides forms and concentrations of essential proteins, lipids and micronutrients that are otherwise scarce. However, the production of this meat is resource intensive. It requires large quantities of arable land and water, and typically has lower conversion efficiency of farm inputs to edible outputs compared with crops, poultry, aquaculture, dairy and eggs. An additional complication is that the quantity of ancillary products produced during slaughterhouse operations is large and underutilized. Each year, approximately 190 million metric tonnes (MMT) of red meat, including pork, lamb, sheep, veal, beef and goats are produced globally, half of which will be consumed by less than 25% of the population living in developed countries. With demand for meat expected to exceed 376 MMT by 2030, an increase in the adoption of plant-based diets presents an opportunity for the world to re-evaluate how meat can be sustainably produced, with greater emphasis on animal welfare, nutritional value, product safety, better utilization and distribution channels. In this article we consider the role meat plays in the modern diet, its production and consumption, opportunities to improve utilization of the animal, the benefits of incorporating a diverse range of red meat into diets, and the strategies that the meat industry should consider in response to flexitarianism.